Technological Redemption: Responding to the Call of Caritas in Veritate (Hekima Review, 2016)
Technological development is one of the ways through which the human race continues to respond to God’s injunction at creation to “fill the earth and subdue it” (Gen. 1:28). Through technology, human beings have been able to discover more about themselves and about the other aspects of creation. Technology is an integral aspect of life in our contemporary world, assisting us to perform many tasks, from the most basic to the most complex. The benefits of technology are evident in so many spheres of our human existence and this has caused us to double our efforts towards achieving greater technological progress. Alternatively, the pursuit of technological progress for the wrong motives is laden with devastating consequences. This paper draws insights from Pope Benedict XVI’s encyclical Caritas in Veritate with the aim of proposing a more appropriate conception and utilization of technology towards integral human development